Analisis Strategis Sistem Pengelolaan Repong Damar di Pesisir Krui, Lampung - Wijayanto, Nurheni (Institut Pertanian Bogor (IPB University), 2002)
Main objective of this research was to identify dominant factors, which determined management system of Repong Damar (SPRD). SPRD was strategically complex and dynamic. Through system approach with SWOT analysis, AHP and Liker Scale, this research identified its dominant factors. Dominant factors, which determined SPRD goals, are land suitability, ecosystem functions, biodiversity, household economy insurance, trading practice and investment inputs. Furthermore, SPRD sustainability was supported by inheritance institution, indigenous knowledge’s, and ownership, which constitute social status symbol. Development strategy of SPRD was determined by community organizations strength and self-resilience, availability of road infrastructure, and law enforcement on farmers rights.